2018
DOI: 10.1016/j.neuropharm.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

CaV3.1 isoform of T-type calcium channels supports excitability of rat and mouse ventral tegmental area neurons

Abstract: Recent data have implicated voltage-gated calcium channels in the regulation of the excitability of neurons within the mesolimbic reward system. While the attention of most research has centered on high voltage L-type calcium channel activity, the presence and role of the low voltage-gated T-type calcium channel (T-channels) has not been well explored. Hence, we investigated T-channel properties in the neurons of the ventral tegmental area (VTA) utilizing wild-type (WT) rats and mice, Ca3.1 knock-out (KO) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Given that previous studies have shown hyperpolarization-induced rebound burst firing in a subset of VTA dopamine and non-dopamine neurons mediated by I h (Tateno and Robinson, 2011) or T-type calcium channels (Tracy et al, 2018, Woodward et al, 2019), we next tested the extent to which rebound firing occurs in the three classes of VTA neurons. After holding the resting membrane potential at −100 mV for 1 sec and then releasing that clamp, approximately 25% of VGluT2 + VGaT + neurons showed rebound firing with short bursts of 2-4 APs (12/48 neurons, 10 mice; Figure 5), and this response was stable over repeated trials (Figure 5-suplement figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Given that previous studies have shown hyperpolarization-induced rebound burst firing in a subset of VTA dopamine and non-dopamine neurons mediated by I h (Tateno and Robinson, 2011) or T-type calcium channels (Tracy et al, 2018, Woodward et al, 2019), we next tested the extent to which rebound firing occurs in the three classes of VTA neurons. After holding the resting membrane potential at −100 mV for 1 sec and then releasing that clamp, approximately 25% of VGluT2 + VGaT + neurons showed rebound firing with short bursts of 2-4 APs (12/48 neurons, 10 mice; Figure 5), and this response was stable over repeated trials (Figure 5-suplement figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent patch-clamp recordings in acute VTA brain slices from WT rats clearly demonstrated expression of classic T-type currents that underlie post-inhibitory rebound burst firing in a subset of VTA neurons (Tracy et al, 2018). However, it is well known that the VTA contains heterogeneous populations of dopaminergic neurons, as well as both inhibitory and excitatory interneurons, all of which play critical roles in regulating motivated behaviors (Morales and Margolis, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we confirm that VTA GABAergic neurons heterogeneously display a voltage sag characteristic of an Ih current at hyperpolarizing potentials, though it is worth noting that among our sample population, Type 2 neurons almost ubiquitously showed a voltage sag upon hyperpolarization. It is also worth noting that for practical reasons all recordings in this and our previuos study (Tracy et al, 2018) were done at room temperature. However, previous studies reported strong temperature dependence of both Ih and T-channel activation (Vargas and Lucero, 1999; Iftinca et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cav3.1 subunits were reported to be important in weight maintenance and sleep/wake activity, which indicated that Cav3.1 could be a potential antiobesity target [134]. In another report, knockdown of Cav3.1 or its inhibition significantly decreased neuronal excitability in the ventral tegmental area, as a result of decreased T-type currents and rebound burst firing in mouse or rat neurons [135]. Alpha(1G)-deficient mice are resistant to absence seizure due to the lack of burst firing in thalamocortical relay neurons [136], while Cav3.1 overexpression was reported to induce absence seizure [137].…”
Section: Cav31mentioning
confidence: 98%